Unravelling the Interplay of Public Debt, Inflation and Unemployment on Poverty in Malaysia: A Comprehensive Examination - Sulong, Amri; Raja Yusof, Raja Nor Azuwah (Journal of Social Transformation and Regional Development, 2023)
This study addresses a critical gap in the existing body of research by exploring the relationship between macroeconomic variables and poverty in Malaysia from 1992 to 2022. Employing the Fully Modified Ordinary Least Squares (FMOLS) method, the research investigates the impact of three key independent variables - unemployment, public debt, and inflation - on the dependent variable, the poverty rate. The findings reveal significant insights: unemployment positively affects the poverty rate, underlining the vulnerability of unemployed individuals to poverty. In contrast, public debt emerges as a negative determinant of poverty, emphasizing the importance of prudent fiscal management for poverty reduction. Intriguingly, inflation does not exhibit a statistically significant association with the poverty rate. These results offer a valuable contribution to the limited macroeconomic studies on poverty in Malaysia, shedding light on the intricate dynamics between economic variables and poverty, and provide valuable guidance for policymakers and researchers alike in the pursuit of targeted poverty alleviation strategies tailored to the Malaysian context.